2007
DOI: 10.4142/jvs.2007.8.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of canine cutaneous tumors in Korea

Abstract: Over the 42 month period from January 2003 to June 2006, a total of 2,952 canine biopsy specimens were received from the Veterinary Medical Teaching Hospital of Seoul National University and from veterinary practitioners across the nation. Out of these, 748 (25.34%) cases were diagnosed as canine cutaneous tumors in the Department of Veterinary Pathology, College of Veterinary Medicine, Seoul National University, Korea. Thirty-eight different types of cutaneous tumors were identified and categorized into epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 13 publications
12
77
2
9
Order By: Relevance
“…In this study, the frequency of CLs was higher than HCTs. Studies on the prevalence of skin tumours in dogs show that the frequency of HCTs is greater than CLs, but in these cases, only histology was used as a diagnostic tool (Kaldrymidou et al 2002, Pakhrin et al 2007). The diagnosis of PCT, LHS and TVT using IHC (5.2%, 9/172, 3.5%, 6/172 and 4.1%, 7/172, respectively) was greater than the diagnoses using only histology (1.74%, 3/172, 1.17%, 2/172 and 0.06%, 1/172, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the frequency of CLs was higher than HCTs. Studies on the prevalence of skin tumours in dogs show that the frequency of HCTs is greater than CLs, but in these cases, only histology was used as a diagnostic tool (Kaldrymidou et al 2002, Pakhrin et al 2007). The diagnosis of PCT, LHS and TVT using IHC (5.2%, 9/172, 3.5%, 6/172 and 4.1%, 7/172, respectively) was greater than the diagnoses using only histology (1.74%, 3/172, 1.17%, 2/172 and 0.06%, 1/172, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Their average diameter is 0.5-3.0 cm and the lesions are generally well circumscribed. Benign lesions may ulcerate and become infected, possibly resulting in their acute presentation but are rarely adherent or fixed to surrounding structures [11,12] . The canine perianal region has different kinds of glands, such as sebaceous glands, perianal (hepatoid) glands, and apocrine glands of the anal sac.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Mikaelian and Gross (2002) mentioned that males were more affected than females by canine keloidal fibroma. However, Mukaratirwa et al (2005) and Pakhrin et al (2007) concluded that, for all classes of canine skin tumors, the sex of the dog did not has any significant influence on the likelihood of developing a tumor. Additionally, Ginel et al (2010) mentioned that when all the sebaceous gland tumors were grouped and analysed, no sex difference was found although estrogen and progesterone receptor expression was reduced in some canine sebaceous gland tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous fibroma was rarely diagnosed in dogs. It comprised 2.8% of the total diagnosed canine skin neoplasms (Pakhrin et al, 2007). Several methods have been used for treatment of canine skin neoplasms.…”
Section: Introductionmentioning
confidence: 99%